Treatment of acute myocardial infarction in Peru and its relationship with in-hospital adverse events: results from the Second Peruvian Registry of ST-segment elevation myocardial infarction (PERSTEMI-II). - Chacón-Diaz, Manuel (2021)
Background. ST-segment elevation myocardial infarction (STEMI), is an important cause of morbidity and mortality worldwide, and myocardial reperfusion, when adequate, reduces the complications of this entity. The aim of the study was to describe the clinical and treatment characteristics of STEMI in Peru and the relationship of successful reperfusion with in-hospital adverse events. Materials and methods. Prospective, multicenter cohort of STEMI patients attended during 2020 in public hospitals in Peru. We evaluated the clinical, therapeutic characteristics and in-hospital adverse events, also the relationship between successful reperfusion and adverse events. Results. A total of 374 patients were included, 69.5% in Lima and Callao. Fibrinolysis was used in 37% of cases (pharmacoinvasive 26% and alone lysis 11%), primary angioplasty with < 12 hours of evolution in 20%, late angioplasty in 9% and 34% did not access adequate reperfusion therapies, mainly due to late presentation. Ischemia time was longer in patients with primary angioplasty compared to fibrinolysis (median 7.7 hours (RIQ 5-10) and 4 hours (RIQ 2.3-5.5) respectively). Mortality was 8.5%, the incidence of post-infarction heart failure was 27.8% and of cardiogenic shock 11.5%. Successful reperfusion was associated with lower cardiovascular mortality (RR:0.28; 95%CI: 0.12-0.66, p=0.003) and lower incidence of heart failure during hospitalization (RR: 0.61; 95%CI: 0.43-0.85, p=0.004). Conclusions. Fibrinolysis continues to be the most frequent reperfusion therapy in public hospitals in Peru. Shorter ischemia-to-reperfusion time was associated with reperfusion success, and in turn with fewer in-hospital adverse events.